Empathy for people with similar experiences: Can the perception-action model explain empathy impairments after traumatic brain injury?. Issue 1 (2nd January 2020) - Osborne-Crowley, Katherine; Wilson, Emily; De Blasio, Frances; Wearne, Travis; Rushby, Jacqueline; McDonald, Skye
ABSTRACT: Introduction : A significant proportion of people with traumatic brain injury (TBI) report low levels of empathy, yet there is a paucity of research investigating the mechanisms which underpin this. In this study, we investigated empathy after TBI through the lens of the perception-action model of empathy. Specifically, we looked at the effect of similarity of experience on self-reported empathy and skin conductance in participants with TBI and controls. Method : Thirty people with a traumatic brain injury and 30 matched healthy controls initially recounted three emotional events they had experienced in the past (one happy, one angry and one sad). Then, at a second visit, participants heard three stories which were written to be similar their own stories and three which were based on someone else's stories. We recorded skin conductance while participants listened and then collected self-reported levels of empathy for protagonists in the stories. Results : We found that self-reported empathy, but not skin conductance levels, was greater for similar compared to dissimilar stories. Further, participants with TBI were able to empathise with others despite having markedly reduced autonomic arousal and overall impairment in cognitive functioning. Conclusions : Our results suggest that the PAM has relevance with respect to explaining self-reported empathy for the experiences of others, but cannot explain the role of physiological responses associated with empathy. Further, our results suggest that intact cognitive functioning and physiological responses are not necessary for normal experiences of empathy after TBI.